Preconditions and Peculiarities of Implementing the Meta-Disciplinary Technologies in Primary School Teaching - Y. Y. Khan (Образование и наука)
The Federal State Educational Standards require the implementa- tion of meta-subject technologies in comprehensive schools. The research is aimed at defining the prerequisites for assimilating the above technologies, and the specif- ics of their implementation and adaptation in the primary school teaching. The author points out the universal character of meta-subject tech- nologies regarding the different categories of children; the idea being the most relevant due to the multi-level educational integration and introduction of the inclusive teaching. To illustrate the modeling of the meta-technology and its application to the school subjects, the author takes the philology sphere. The process of simultane- ous addressing the piece of literature and work of art creates the associative edu- cational environment raising the collective creativity and resulting in the joint intel- lectual and esthetic experience of students and teaches. The research findings demonstrate the impact of meta-disciplinary technologies on students’ cognitive activity; its positive dynamics proves the effectiveness of given technologies.